Extending the Theory of Planned Behavior to examine the role of anticipated negative emotions on channel intention: The case of an embarrassing product. (May 2017) - Londono, Juan Carlos; Davies, Keri; Elms, Jonathan
Abstract: The Theory of Planned Behavior (TPB) is successful in predicting consumer intentions for a wide variety of products and behaviors. However, little is known about how effective the TPB is when the behavior under study is embarrassing. To this end, this paper extends the TPB to create a conceptual model to examine the role of anticipated negative emotions on channel intention. An empirical study was conducted whereby the model was tested using survey data on the purchase of Regaine (a hair loss product that is embarrassing to buy) in Boots (a well-known UK multichannel drugstore). The embarrassing nature of Regaine created differences in the importance that emotions played when consumers intend to purchase using face-to-face channels (such as the physical drugstore) as against multichannel options or the internet. The results were analyzed using partial least squares structural equation modelling (PLS-SEM). The effectiveness of the TPB was improved. The variance explained (R 2 to intention) was 0.44% for the total sample, 49% for the drugstore, 58.4% for the internet, and 42.5% for multichannel.